Endothelial TFEB (Transcription Factor EB) Improves Glucose Tolerance via Upregulation of IRS (Insulin Receptor Substrate) 1 and IRS2. Issue 2 (February 2021) - Sun, Jinjian; Lu, Haocheng; Liang, Wenying; Zhao, Guizhen; Ren, Lu; Hu, Die; Chang, Ziyi; Liu, Yuhao; Garcia-Barrio, Minerva T.; Zhang, Jifeng; Chen, Y. Eugene; Fan, Yanbo
Abstract : Objective: Vascular endothelial cells (ECs) play a critical role in maintaining vascular homeostasis. Aberrant EC metabolism leads to vascular dysfunction and metabolic diseases. TFEB (transcription factor EB), a master regulator of lysosome biogenesis and autophagy, has protective effects on vascular inflammation and atherosclerosis. However, the role of endothelial TFEB in metabolism remains to be explored. In this study, we sought to investigate the role of endothelial TFEB in glucose metabolism and underlying molecular mechanisms. Approach and Results: To determine whether endothelial TFEB is critical for glucose metabolism in vivo, we utilized EC-selective TFEB knockout and EC-selective TFEB transgenic mice fed a high-fat diet. EC-selective TFEB knockout mice exhibited significantly impaired glucose tolerance compared with control mice. Consistently, EC-selective TFEB transgenic mice showed improved glucose tolerance. In primary human ECs, small interfering RNA-mediated TFEB knockdown blunts Akt (AKT serine/threonine kinase) signaling. Adenovirus-mediated overexpression of TFEB consistently activates Akt and significantly increases glucose uptake in ECs. Mechanistically, TFEB upregulates IRS1 and IRS2 (insulin receptor substrate 1 and 2). TFEB increases IRS2 transcription measured by reporter gene and chromatin immunoprecipitation assays. Furthermore, we found that TFEB increases IRS1 protein via downregulation of microRNAs (miR-335, miR-495, and miR-548o). In vivo, Akt signaling in the skeletal muscle and adipose tissue was significantly impaired in EC-selective TFEB knockout mice and consistently improved in EC-selective TFEB transgenic mice on high-fat diet. Conclusions: Our data revealed a critical role of TFEB in endothelial metabolism and suggest that TFEB constitutes a potential molecular target for the treatment of vascular and metabolic diseases. Abstract : Supplemental Digital Content is available in the text.